Catalyst for thermally stable degradation of VOCs (volatile organic compounds) as well as preparation method and application of catalyst

By introducing specific first and second additives into the catalyst, a multi-effect composite additive is formed, and the existing catalysts have poor purification effect and short service life under high temperature and high humidity environments are solved, thereby achieving efficient VOCs Remove and operate stably for a long time.

CN119425726APending Publication Date: 2025-02-14ZHEJIANG TIANLAN ENVIRONMENTAL PROTECTION TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411584635.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing catalysts used to degrade VOCs have poor purification effect and short service life under high temperature and high humidity environments.

Method used

By introducing a combination of a specific first additive and a second additive into the catalyst, a multi-effect composite additive is formed, which improves the resistance to high temperature sintering of the catalyst and strong bonding of the active components, and enhances the synergistic catalysis.

Benefits of technology

It achieves long-term and stable operation under high temperature and high humidity conditions, improves the removal effect of VOCs, extends the service life of the catalyst, and has a purification efficiency of more than 98.6% under water vapor conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123992980000141
    Figure BDA0005123992980000141
Patent Text Reader

Abstract

The invention relates to a catalyst for thermally stably degrading VOCs (volatile organic compounds) as well as a preparation method and application thereof, in particular to the field of VOCs purification, and the catalyst comprises a substrate as well as an auxiliary agent and an active component which are arranged on the substrate, the auxiliary agent comprises a first auxiliary agent and a second auxiliary agent; the first auxiliary agent comprises a cobalt-containing auxiliary agent and / or an iron-containing auxiliary agent; according to the catalyst provided by the invention, the specific first auxiliary agent and the second auxiliary agent are introduced into the catalyst and are matched, so that oxygen molecules can be quickly adsorbed and activated in the VOCs catalytic purification process and do not form a catalytic synergistic center with active components, and the removal effect of the VOCs is improved; and long-term stable operation of the catalyst under severe conditions of high temperature, high humidity and the like is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of VOCs purification, and in particular to a thermally stable catalyst for degrading VOCs, and a preparation method and application thereof. Background Art

[0002] At present, among a series of technical means to control VOCs emissions, catalytic combustion technology has become the mainstream technology for achieving VOCs emission standards due to its advantages of high purification efficiency and low energy consumption. Therefore, catalysts generally use palladium and platinum as active components, and their effective service life is about 12-15 months. However, in the pharmaceutical, chlor-alkali industry, garbage, solid waste incineration and other working conditions where the waste gas composition is complex and the moisture content is high, the catalyst life is shortened to 5-7 months.

[0003] At present, domestic and foreign researchers' research on improving catalyst performance and extending catalyst life is mainly focused on the reconstruction and dosage of precious metals. For example, CN111185221A discloses a PdAg alloy-loaded Ti-SBA-15 catalyst and its preparation method and application. The catalyst is prepared by dissolving surfactant P123 in hydrochloric acid and stirring at 30-150°C to obtain a solution; adding tetraethyl orthosilicate and a Ti source dropwise to the above solution, stirring at 30-150°C, then aging the resulting suspension A at 40-150°C, filtering, washing, and drying, and then calcining at 500-550°C to obtain a Ti-SBA-15 carrier; dissolving a Pd precursor, an Ag precursor, and a Ti-SBA-15 carrier in ultrapure water, stirring at room temperature to obtain a suspension B, adding a NaBH4 solution and stirring, and filtering, washing, and drying to obtain the Ti-SBA-15 carrier.

[0004] CN101733165A discloses a preparation method and application of a low-content precious metal monolithic catalyst. The invention adopts a chemical plating method, utilizes hydrazine or sodium hypophosphite as a reducing agent, and generates an oxidation-reduction reaction with palladium chloride or chloroplatinic acid in a plating solution. At the same time, under the autocatalytic action of Pd or Pt, metal Pd and / or Pt is directly deposited on the surface of the cordierite honeycomb ceramic pores, thereby obtaining a loaded low-content Pt and / or Pd precious metal monolithic catalyst.

[0005] CN113797961A discloses a RuCe / ZSM-5 molecular sieve catalyst and its preparation method and application, first hydrothermally synthesizes a Na-ZSM-5 molecular sieve with a micro-mesoporous structure, then converts the Na-ZSM-5 molecular sieve into H-ZSM-5 by ion exchange, uses H-ZSM-5 as a carrier, loads Ru and Ce precursor solutions onto H-ZSM-5 by a citric acid sol-gel method, and then prepares a RuCe / ZSM-5 molecular sieve catalyst by roasting. The RuCe-ZSM-5 synthesized by the hydrothermal crystallization method in this scheme has a multi-level pore structure, can effectively reduce the mass transfer resistance of chlorobenzene on the catalyst, greatly improves the chlorobenzene conversion performance, reaches 98.4% at 275°C chlorobenzene conversion rate, and has good anti-chlorine poisoning performance. However, the hydrothermal stability of the molecular sieve is poor, and its microscopic ordered shape and structure are prone to collapse under high temperature and high humidity, resulting in the catalyst being unable to operate for a long time under the above environment. In addition, the molecular sieve carrier has a high degree of order, few surface defects, and weak interaction with the precious metal, and cannot form a strong metal-carrier interaction, making it difficult to prevent the clustering or granulation of precious metal ions at high temperatures.

[0006] In summary, the existing catalysts for degrading VOCs still have the defects of poor purification effect and short service life in high temperature and high humidity environments. Summary of the invention

[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a thermally stable catalyst for degrading VOCs, a preparation method and use thereof, so as to solve the defects of catalysts used for degrading VOCs, such as poor purification effect and short service life under high temperature and high humidity environment.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a thermally stable catalyst for degrading VOCs, the catalyst comprising: a substrate and an auxiliary agent and an active component on the substrate;

[0010] The auxiliary agent includes a first auxiliary agent and a second auxiliary agent;

[0011] The first additive includes a cobalt-containing additive and / or an iron-containing additive; the second additive includes an aluminum-based additive

[0012] The catalyst provided by the present invention, by introducing a combination of a specific first auxiliary agent and a second auxiliary agent into the catalyst, can quickly adsorb and activate oxygen molecules during the catalytic purification of VOCs and does not form a catalytic synergistic center with the active components, thereby improving the removal effect of VOCs and facilitating the long-term stable operation of the catalyst under adverse conditions such as high temperature and high humidity.

[0013] As a preferred technical solution of the present invention, the content of the effective element of the first auxiliary agent is 0.2-8% of the total mass of the catalyst;

[0014] Preferably, the effective elements include cobalt and / or iron.

[0015] As a preferred technical solution of the present invention, the active component accounts for 0.002-1.5% of the total mass of the catalyst.

[0016] As a preferred technical solution of the present invention, the substrate includes honeycomb mullite and / or honeycomb cordierite.

[0017] Preferably, the first auxiliary agent comprises one or a combination of at least two of cobalt trioxide, cobalt oxide, ferrosoferric oxide or ferric oxide.

[0018] Preferably, the second auxiliary agent comprises alumina and / or pseudo-boehmite.

[0019] As a preferred technical solution of the present invention, the active component includes one or a combination of at least two of platinum, ruthenium or palladium.

[0020] In a second aspect, the present invention provides a method for preparing the catalyst according to the first aspect, the method comprising: first stirring and mixing a first auxiliary agent dispersion liquid and a second auxiliary agent dispersion liquid, and then first calcining to obtain a composite auxiliary agent;

[0021] The composite auxiliary agent and the active component dispersion are subjected to a second stirring and mixing, and then subjected to a second calcination to obtain a catalyst composite powder;

[0022] The catalyst composite powder, the second auxiliary agent and the concentrated acid are ball-milled to obtain a gelled mixed solution;

[0023] The gelled mixed liquid and the catalyst substrate are combined, and then subjected to a third calcination to obtain a thermally stable catalyst for degrading VOCs.

[0024] As a preferred technical solution of the present invention, the first auxiliary agent dispersion liquid is obtained by dispersing the first auxiliary agent in a first solvent.

[0025] Preferably, the second auxiliary agent dispersion is obtained by dispersing the second auxiliary agent in a second solvent.

[0026] As a preferred technical solution of the present invention, the mass ratio of the first auxiliary agent to the second auxiliary agent in the first auxiliary agent dispersion and the second auxiliary agent dispersion is (0.1-0.4):1.

[0027] As a preferred technical solution of the present invention, the temperature of the first calcination is 600-850°C.

[0028] Preferably, the first calcination time is 2-10 hours.

[0029] As a preferred technical solution of the present invention, the active component dispersion is obtained by dispersing the active substance in a third solvent.

[0030] Preferably, the active material comprises one or a combination of at least two of platinum nitrate, tetraamine platinum nitrate, chloroplatinic acid, tetraamine platinum chloride, ruthenium chloride, nitrosyl ruthenium nitrate, palladium chloride, palladium nitrate or tetraamine palladium nitrate.

[0031] As a preferred technical solution of the present invention, the mass ratio of the composite auxiliary agent to the active substance in the active component dispersion is 1:(0.01-0.5).

[0032] As a preferred technical solution of the present invention, the temperature of the second calcination is 400-600°C.

[0033] Preferably, the second calcination time is 1-5 hours.

[0034] As a preferred technical solution of the present invention, the mass ratio of concentrated acid to the second auxiliary agent in the ball milling is (0.01-0.08):1.

[0035] Preferably, the mass ratio of the second auxiliary agent to the catalyst composite powder in the ball milling is (0.05-0.5):1.

[0036] As a preferred technical solution of the present invention, the ball milling time is 30-120 minutes.

[0037] Preferably, the mass ratio of grinding balls to materials in the ball mill is (2-20):1.

[0038] As a preferred technical solution of the present invention, the temperature of the third calcination is 400-600°C.

[0039] Preferably, the third calcination time is 1-5 hours.

[0040] In a third aspect, the present invention provides a use of the catalyst as described in the first aspect, wherein the use comprises using the catalyst to purify volatile organic compounds.

[0041] As a preferred technical solution of the present invention, the volatile organic compound includes one or a combination of at least two of toluene, propylene or xylene;

[0042] Preferably, the water vapor content in the volatile organic matter is ≥5%.

[0043] Compared with the prior art solutions, the present invention has the following beneficial effects:

[0044] (1) Through the solid-solid dual-phase high-temperature rapid coupling between the first additive and the second additive, a multi-effect composite additive is formed. The composite additive has the characteristics of high-temperature sintering resistance, strong bonding of active components, and enhanced synergistic catalysis. It can provide a large number of bonding points, and form various types of precious metal-oxygen-transition metal structures through strong bonding with precious metals to stabilize the active components; the oxygen vacancies in the multi-effect composite additive can also quickly adsorb and activate oxygen molecules during the reaction, and form a catalytic synergistic center with the active components, thereby increasing the unit conversion rate of VOCs and carbon monoxide, and achieving long-term stable operation under harsh conditions such as high temperature and high humidity.

[0045] (2) By directly modifying the second auxiliary agent by gelling, the addition of sol containing other components can be reduced, and the catalyst composite powder can be ball-milled for secondary enhancement, which can improve the homogeneity and integration between the solid-liquid phases, and finally overcome the problem of local gap expansion in the coating caused by low component matching rate and poor homogeneity between the composite powder and the sol during the high-temperature curing stage, further enhance the hydrothermal stability of the catalyst, and improve the service life of the catalyst under high-humidity flue gas. Under water vapor-free conditions, the purification efficiency can reach more than 98.6%. When the volume percentage of water vapor is 5%, it still has a high purification effect, and the purification rate can reach more than 93.8%. At the same time, the shedding rate of the coating during the purification process is ≤9.8%. DETAILED DESCRIPTION

[0046] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0047] This embodiment provides a thermally stable catalyst for degrading VOCs, the catalyst comprising: a substrate and an auxiliary agent and an active component on the substrate;

[0048] The auxiliary agent includes a first auxiliary agent and a second auxiliary agent;

[0049] The first auxiliary agent includes a cobalt-containing auxiliary agent and / or an iron-containing auxiliary agent; the second auxiliary agent includes an aluminum-based auxiliary agent.

[0050] Among them, the content of the effective element of the first auxiliary agent is 0.2-8% of the total mass of the catalyst, for example, it can be 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%, etc., but is not limited to the listed values, and other unlisted values ​​within this range also meet the requirements.

[0051] Wherein, the effective elements include cobalt and / or iron.

[0052] Wherein, the active component is 0.002-1.5% of the total mass of the catalyst, for example, it can be 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4% or 1.5%, etc., but is not limited to the listed values, and other unlisted values ​​within this range also meet the requirements.

[0053] Wherein, the substrate comprises honeycomb mullite and / or honeycomb cordierite.

[0054] Wherein, the first auxiliary agent includes one or a combination of at least two of cobalt trioxide, cobalt oxide, ferroferric oxide or ferric oxide.

[0055] Illustratively, the combination of the first auxiliary agent is a combination of cobaltous oxide and cobalt oxide, a combination of cobalt oxide and ferrosoferric oxide, a combination of ferrosoferric oxide and ferric oxide, a combination of cobalt oxide and ferrosoferric oxide, and the like.

[0056] Wherein, the second auxiliary agent includes alumina and / or pseudo-boehmite.

[0057] The active component includes one or a combination of at least two of platinum, ruthenium or palladium.

[0058] Illustratively, the combination of active components may be selected as a combination of platinum and ruthenium, a combination of ruthenium and palladium, a combination of platinum and palladium, and the like.

[0059] Furthermore, the present invention provides a method for preparing the aforementioned catalyst, the preparation method comprising:

[0060] The first auxiliary agent dispersion liquid and the second auxiliary agent dispersion liquid are first stirred and mixed, and then first calcined to obtain a composite auxiliary agent;

[0061] The composite auxiliary agent and the active component dispersion are subjected to a second stirring and mixing, and then subjected to a second calcination to obtain a catalyst composite powder;

[0062] The catalyst composite powder, the second auxiliary agent and the concentrated acid are ball-milled to obtain a gelled mixed solution;

[0063] The gelled mixed liquid and the catalyst substrate are combined, and then subjected to a third calcination to obtain a thermally stable catalyst for degrading VOCs.

[0064] The first auxiliary agent dispersion is obtained by dispersing the first auxiliary agent in a first solvent.

[0065] In the present invention, the first auxiliary agent used in the preparation process is a limited metal powder of cobalt trioxide, cobalt oxide, ferrosoferric oxide or ferric oxide.

[0066] The second auxiliary agent dispersion is prepared by dispersing the second auxiliary agent in a second solvent.

[0067] In the present invention, the second auxiliary agent used in the preparation process is a powder of a specified alumina and / or pseudo-boehmite.

[0068] Among them, the mass ratio of the first auxiliary agent and the second auxiliary agent in the first auxiliary agent dispersion and the second auxiliary agent dispersion is (0.1-0.4):1, for example, it can be 0.1:1, 0.12:1, 0.14:1, 0.16:1, 0.18:1, 0.2:1, 0.22:1, 0.24:1, 0.26:1, 0.28:1, 0.3:1, 0.32:1, 0.34:1, 0.36:1, 0.38:1 or 0.4:1, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0069] Wherein, the temperature of the first calcination is 600-850°C, for example, it can be 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C or 850°C, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0070] Wherein, the first calcination time is 2-10h, for example, it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h or 10h, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0071] The active component dispersion is obtained by dispersing the active substance in a third solvent.

[0072] The active material comprises one or a combination of at least two of platinum nitrate, tetraamine platinum nitrate, chloroplatinic acid, tetraamine platinum chloride, ruthenium chloride, nitrosyl ruthenium nitrate, palladium chloride, palladium nitrate or tetraamine palladium nitrate.

[0073] Exemplarily, combinations of active substances include a combination of platinum nitrate and tetraamineplatinum nitrate, a combination of chloroplatinic acid and tetraamineplatinic chloride, a combination of tetraamineplatinic chloride and ruthenium chloride, a combination of nitrosylruthenium nitrate and palladium chloride, a combination of palladium nitrate and tetraaminepalladium nitrate, a combination of chloroplatinic acid and nitrosylruthenium nitrate, a combination of tetraamineplatinum nitrate and palladium nitrate, and the like.

[0074] Among them, the mass ratio of the composite auxiliary agent to the active substance in the active component dispersion is 1:(0.01-0.5), for example, it can be 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45 or 1:0.5, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0075] Wherein, the temperature of the second calcination is 400-600°C, for example, it can be 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C or 600°C, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0076] The second calcination time is 1-5 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0077] Wherein, the mass ratio of concentrated acid to the second auxiliary agent in the ball milling is (0.01-0.08):1, for example, it can be 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1, 0.05:1, 0.055:1, 0.06:1, 0.065:1, 0.07:1, 0.075:1 or 0.08:1, etc., but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0078] In the present invention, the concentrated acid used in the ball milling can be selected from concentrated nitric acid, concentrated sulfuric acid or concentrated hydrochloric acid and other commonly used concentrated acids in the art.

[0079] Among them, the mass ratio of the second auxiliary agent and the catalyst composite powder in the ball mill is (0.05-0.5):1, for example, it can be 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1 or 0.5:1, but is not limited to the listed values, and other unlisted values ​​within this range also meet the requirements.

[0080] The ball milling time is 30-120 min, for example, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0081] The mass ratio of the grinding balls to the materials in the ball mill is (2-20):1, for example, 2:1, 4:1, 6:1, 8:1, 10:1, 12:1, 14:1, 16:1, 18:1 or 20:1, etc., but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0082] Among them, the temperature of the third calcination is 400-600℃, for example, it can be 400℃, 420℃, 440℃, 460℃, 480℃, 500℃, 520℃, 540℃, 560℃, 580℃ or 600℃, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0083] The third calcination time is 1-5 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, but is not limited to the listed values. Other values ​​not listed in the range also meet the requirements.

[0084] In the present invention, the dispersion methods in the preparation process include but are not limited to stirring, ultrasound, shearing and other methods commonly used in the art for dispersing solids in liquids.

[0085] In the present invention, during the preparation process, the first solvent, the second solvent and the third solvent used can be selected from commonly used solvents in the art such as water.

[0086] In the present invention, the catalyst substrate can be soaked in an acid solution with a mass concentration of 5-10% for 30-60 minutes before use, and then optionally washed and dried for standby use.

[0087] Wherein, the acid solution used in the soaking treatment includes nitric acid and / or sulfuric acid.

[0088] Furthermore, the present invention provides a use of the aforementioned catalyst, which includes using the catalyst to purify volatile organic compounds.

[0089] Wherein, the volatile organic matter includes one or a combination of at least two of toluene, propylene or xylene.

[0090] Wherein, the water vapor content in the volatile organic matter is ≥5%.

[0091] In order to illustrate the good purification effect that the catalyst provided by the present invention can achieve for volatile organic compounds, the present invention uses actual examples for illustration, as follows:

[0092] Example 1

[0093] This embodiment provides a thermally stable catalyst for degrading VOCs, and the preparation process is as follows:

[0094] (1) Soaking the honeycomb cordierite in a 5 wt % dilute nitric acid solution for 30 min, then washing it twice with deionized water, and drying it at 120° C. for 2 h to obtain a pretreated catalyst substrate for later use;

[0095] (2) dispersing 4 g of the first auxiliary agent, which is cobalt oxide, in 100 g of deionized water and stirring to obtain a first auxiliary agent dispersion; dispersing 28 g of the second auxiliary agent, which is aluminum oxide, in 100 g of deionized water and stirring to obtain a second auxiliary agent dispersion; pouring the second auxiliary agent dispersion into the first auxiliary agent dispersion, stirring for 30 min, drying at 120° C., and finally calcining at 800° C. for 4 h to obtain a composite auxiliary agent;

[0096] (3) dispersing 30 g of the composite auxiliary agent in 100 g of deionized water to obtain a mixed solution; dissolving 2 g of palladium nitrate in 5 g of deionized water, stirring, and obtaining an active component dispersion (the mass concentration of the palladium element is 15 wt%); then adding the active component dispersion to the mixed solution, stirring, drying at 120° C., and finally calcining at 450° C. for 3 h to obtain a catalyst composite powder;

[0097] (4) 3 g of the second auxiliary agent, namely pseudo-boehmite, and 0.2 g of concentrated nitric acid were added to 100 g of deionized water, and stirred thoroughly. Then, 20 g of the catalyst composite powder was added, and ball milling was performed for 60 min to obtain a gelled mixed solution. The catalyst substrate of step (1) was immersed in the gelled mixed solution, coated by negative pressure coating, dried at 120° C., and finally calcined at 450° C. for 2 h to obtain a monolithic catalyst.

[0098] Example 2

[0099] This embodiment provides a thermally stable catalyst for degrading VOCs, and the preparation process is as follows:

[0100] (1) Soaking the honeycomb cordierite in a 5 wt % dilute nitric acid solution for 30 min, then washing it twice with deionized water, and drying it at 120° C. for 2 h to obtain a pretreated catalyst substrate for later use;

[0101] (2) dispersing 4 g of a first auxiliary agent, namely cobalt oxide, in 100 g of deionized water and stirring to obtain a first auxiliary agent dispersion; dispersing 28 g of a second auxiliary agent, namely aluminum oxide, in 100 g of deionized water and stirring to obtain a second auxiliary agent dispersion; pouring the second auxiliary agent dispersion into the first auxiliary agent dispersion, stirring for 30 min, drying at 120° C., and finally high-temperature treating at 800° C. for 4 h to obtain a composite auxiliary agent;

[0102] (3) dispersing 30 g of the composite auxiliary agent in 100 g of deionized water to obtain a mixed solution; dissolving 3 g of platinum nitrate in 5 g of deionized water, stirring, and obtaining an active component dispersion (the mass concentration of the platinum element is 10 wt%); then adding the active component dispersion to the mixed solution, stirring, drying at 120° C., and finally calcining at 450° C. for 3 h to obtain a catalyst composite powder;

[0103] (4) 3 g of the second auxiliary agent, namely pseudo-boehmite, and 0.2 g of concentrated nitric acid were added to 100 g of deionized water, stirred thoroughly, and then 20 g of the catalyst composite powder was added, and ball milled for 60 min to obtain a gelled mixed solution. The catalyst substrate in step (1) was immersed in the gelled mixed solution, coated by negative pressure coating, dried at 120° C., and finally calcined at 450° C. for 3 h to obtain a monolithic catalyst.

[0104] Example 3

[0105] This embodiment provides a thermally stable catalyst for degrading VOCs, and the preparation process is as follows:

[0106] (1) Soaking the honeycomb cordierite in a 5 wt % dilute nitric acid solution for 30 min, then washing it twice with deionized water, and drying it at 120° C. for 2 h to obtain a pretreated catalyst substrate for later use;

[0107] (2) Dispersing 4 g of the first additive, which is iron oxide, in 100 g of deionized water and stirring to obtain a first additive dispersion; dispersing 28 g of the second additive, which is aluminum oxide, in 100 g of deionized water and stirring to obtain a second additive dispersion; pouring the second additive dispersion into the first additive dispersion, stirring for 30 min, drying at 120° C., and finally high-temperature treating at 850° C. for 4 h to obtain a composite additive;

[0108] (3) dispersing 30 g of the composite auxiliary agent in 100 g of deionized water to obtain a mixed solution; dissolving 3 g of palladium nitrate in 5 g of deionized water, stirring, and obtaining an active component dispersion (the mass concentration of the palladium element is 10 wt%); then adding the active component dispersion to the mixed solution, stirring, drying at 120° C., and finally calcining at 450° C. for 2.5 h to obtain a catalyst composite powder;

[0109] (4) 3 g of the second auxiliary agent, namely pseudo-boehmite, and 0.2 g of concentrated nitric acid were added to 100 g of deionized water, and stirred thoroughly. Then, 20 g of the catalyst composite powder was added, and ball milling was performed for 60 min to obtain a gelled mixed solution. The catalyst substrate in (1) was immersed in the gelled mixed solution, coated by negative pressure coating, dried at 120° C., and finally calcined at 450° C. for 3 h to obtain a monolithic catalyst.

[0110] Example 4

[0111] This embodiment provides a thermally stable catalyst for degrading VOCs, and the preparation process is as follows:

[0112] (1) Soaking the honeycomb cordierite in a 5 wt % dilute nitric acid solution for 30 min, then washing it twice with deionized water, and drying it at 120° C. for 2 h to obtain a pretreated catalyst substrate for later use;

[0113] (2) dispersing 4 g of a first auxiliary agent, namely cobalt oxide, in 100 g of deionized water and stirring to obtain a first auxiliary agent dispersion; dispersing 28 g of a second auxiliary agent, namely aluminum oxide, in 100 g of deionized water and stirring to obtain a second auxiliary agent dispersion; pouring the second auxiliary agent dispersion into the first auxiliary agent dispersion, stirring for 30 min, drying at 120° C., and finally high-temperature treating at 800° C. for 4 h to obtain a composite auxiliary agent;

[0114] (3) dispersing 30 g of the composite auxiliary agent in 100 g of deionized water to obtain a mixed solution; dissolving 3 g of platinum nitrate in 5 g of deionized water, stirring, and obtaining an active component dispersion (the mass concentration of the platinum element is 10 wt%); then adding the active component dispersion to the mixed solution, stirring, drying at 120° C., and finally calcining at 450° C. for 2.5 h to obtain a catalyst composite powder;

[0115] (4) 3 g of the second auxiliary agent, namely pseudo-boehmite, and 0.2 g of concentrated nitric acid were added to 100 g of deionized water, stirred thoroughly, and then 20 g of the catalyst composite powder was added, and ball milled for 60 min to obtain a gelled mixed solution. The catalyst substrate in (1) was immersed in the gelled mixed solution, coated by negative pressure coating, dried at 120° C., and finally calcined at 450° C. for 2.5 h to obtain a monolithic catalyst.

[0116] Comparative Example 1

[0117] The only difference from Example 1 is that the first auxiliary agent in step (2) is replaced by an equal amount of the second auxiliary agent.

[0118] Comparative Example 2

[0119] The only difference from Example 1 is that the second auxiliary agent in step (2) is replaced by an equal amount of the first auxiliary agent.

[0120] Comparative Example 3

[0121] The only difference from Example 1 is that the second auxiliary agent in step (4) is replaced by an equal amount of the first auxiliary agent.

[0122] Comparative Example 4

[0123] The only difference from Example 1 is that the second auxiliary agent in step (2) and step (4) is replaced by an equal amount of the first auxiliary agent.

[0124] Comparative Example 5

[0125] The only difference from Example 1 is that the first auxiliary agent in step (2) is replaced by an equal amount of chromium oxide.

[0126] Comparative Example 6

[0127] The only difference from Example 1 is that the second auxiliary agent in step (2) and step (4) is replaced by an equal amount of chromium oxide.

[0128] Comparative Example 7

[0129] The only difference from Example 1 is that palladium nitrate is not added in step (3).

[0130] Comparative Example 8

[0131] The only difference from Example 1 is that in step (4), concentrated nitric acid and pseudo-boehmite are not added, that is, gelation is not performed.

[0132] The catalysts obtained in the examples and comparative examples were heated for 15000 h. -1 Under the air velocity conditions, the VOCs were purified under the water vapor conditions of 0 and 5%, where the coating shedding rate refers to the percentage of the area of ​​the additives and active components peeled off on the substrate to the total contact area between the substrate and the additives and active components. The treatment results are detailed in Table 1.

[0133] Table 1

[0134]

[0135] As shown in Table 1, in the scheme provided by the present invention, a multi-effect composite additive is formed by the solid-solid dual-phase high-temperature rapid coupling between the first additive and the second additive. The composite additive also has the characteristics of high-temperature sintering resistance, strong bonding of active components, and enhanced synergistic catalysis. A large number of bonding points can be provided, and various types of precious metal-oxygen-transition metal structures are formed by strong bonding with precious metals to stabilize the active components; the oxygen vacancies in the multi-effect composite additive can also quickly adsorb activated oxygen molecules during the reaction, and form a catalytic synergistic center with the active components to improve the VOCs conversion efficiency. In addition, by directly gelling and modifying the second additive, the addition of sol containing other components can be reduced, and the composite powder of the catalyst is ball-milled for secondary enhancement, which can improve the degree of homogeneous integration between the solid-liquid phase, and finally overcome the problem of local gap expansion of the coating caused by low component matching rate and poor homogeneity between the composite powder and the sol during the high-temperature curing stage, and further enhance the hydrothermal stability of the catalyst.

[0136] It is stated that the present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0137] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0138] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0139] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A thermally stable catalyst for degrading VOCs, characterized in that: The catalyst comprises: a substrate and an auxiliary agent and an active component on the substrate; The auxiliary agent includes a first auxiliary agent and a second auxiliary agent; The first auxiliary agent includes a cobalt-containing auxiliary agent and / or an iron-containing auxiliary agent; the second auxiliary agent includes an aluminum-based auxiliary agent.

2. The catalyst according to claim 1, characterized in that The content of the effective element of the first auxiliary agent is 0.2-8% of the total mass of the catalyst; Preferably, the effective elements include cobalt and / or iron.

3. The catalyst according to claim 1 or 2, characterized in that The active component accounts for 0.002-1.5% of the total mass of the catalyst.

4. The catalyst according to any one of claims 1 to 3, characterized in that The substrate comprises honeycomb mullite and / or honeycomb cordierite; Preferably, the first auxiliary agent comprises one or a combination of at least two of cobalt trioxide, cobalt oxide, ferroferric oxide or ferric oxide; Preferably, the second auxiliary agent comprises alumina and / or pseudo-boehmite.

5. The catalyst according to any one of claims 1 to 4, characterized in that The active component includes one or a combination of at least two of platinum, ruthenium or palladium.

6. A method for preparing the catalyst according to any one of claims 1 to 5, characterized in that: The preparation method comprises: first stirring and mixing a first auxiliary agent dispersion liquid and a second auxiliary agent dispersion liquid, and then first calcining to obtain a composite auxiliary agent; The composite auxiliary agent and the active component dispersion are subjected to a second stirring and mixing, and then subjected to a second calcination to obtain a catalyst composite powder; The catalyst composite powder, the second auxiliary agent and the concentrated acid are ball-milled to obtain a gelled mixed solution; The gelled mixed liquid and the catalyst substrate are combined, and then subjected to a third calcination to obtain a thermally stable catalyst for degrading VOCs.

7. The preparation method according to claim 6, characterized in that: The first auxiliary agent dispersion comprises a first auxiliary agent dispersed in a first solvent; Preferably, the second auxiliary agent dispersion is obtained by dispersing the second auxiliary agent in a second solvent.

8. The preparation method according to claim 6 or 7, characterized in that: The mass ratio of the first auxiliary agent to the second auxiliary agent in the first auxiliary agent dispersion is (0.1-0.4):

1.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The temperature of the first calcination is 600-850°C; Preferably, the first calcination time is 2-10 hours.

10. The preparation method according to any one of claims 6 to 9, characterized in that: The active component dispersion comprises an active substance dispersed in a third solvent; Preferably, the active material comprises one or a combination of at least two of platinum nitrate, tetraamine platinum nitrate, chloroplatinic acid, tetraamine platinum chloride, ruthenium chloride, nitrosyl ruthenium nitrate, palladium chloride, palladium nitrate or tetraamine palladium nitrate.

11. The preparation method according to any one of claims 6 to 10, characterized in that: The mass ratio of the composite auxiliary agent to the active substance in the active component dispersion is 1:(0.01-0.5).

12. The preparation method according to any one of claims 6 to 11, characterized in that: The second calcination temperature is 400-600°C; Preferably, the second calcination time is 1-5 hours.

13. The preparation method according to any one of claims 6 to 12, characterized in that: The mass ratio of the concentrated acid to the second auxiliary agent in the ball milling is (0.01-0.08):1; Preferably, the mass ratio of the second auxiliary agent to the catalyst composite powder in the ball milling is (0.05-0.5):

1.

14. The preparation method according to any one of claims 6 to 13, characterized in that: The ball milling time is 30-120min; Preferably, the mass ratio of grinding balls to materials in the ball mill is (2-20):

1.

15. The preparation method according to any one of claims 6 to 14, characterized in that: The temperature of the third calcination is 400-600°C; Preferably, the third calcination time is 1-5 hours.

16. Use of the catalyst according to any one of claims 1 to 5, comprising using the catalyst to purify volatile organic compounds.

17. The use according to claim 16, characterized in that The volatile organic matter includes one or a combination of at least two of toluene, propylene or xylene; Preferably, the water vapor content in the volatile organic matter is ≥5%.

Citation Information

Patent Citations

  • Preparation method of integral type catalyst with low content of noble metal and application thereof

    CN101733165A

  • PdAg alloy-loaded Ti-SBA-15 catalyst, and preparation method and application thereof

    CN111185221A

  • RuCe / ZSM-5 molecular sieve catalyst as well as preparation method and application thereof

    CN113797961A